2013
DOI: 10.1371/journal.pgen.1003701
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Unfolded Protein and Oxidative Stress Responses through SKN-1/Nrf

Abstract: The Unfolded Protein Response (UPR) maintains homeostasis in the endoplasmic reticulum (ER) and defends against ER stress, an underlying factor in various human diseases. During the UPR, numerous genes are activated that sustain and protect the ER. These responses are known to involve the canonical UPR transcription factors XBP1, ATF4, and ATF6. Here, we show in C. elegans that the conserved stress defense factor SKN-1/Nrf plays a central and essential role in the transcriptional UPR. While SKN-1/Nrf has a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
182
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 90 publications
5
182
1
Order By: Relevance
“…Nrf1 and Nrf3 proteins of this family have been reported to be associated with the ER membrane and nuclear envelope which suggest their involvement in ER-related functions [43,44]. A study in Caenorhabditis elegans [45] revealed that SKN-1, the Nrf ortholog, plays a critical role in resistance to oxidative and ER stress. Moreover, it has been reported that the response mobilized by SKN-1/Nrf under UPR is observed to be overlapping but still distinct from that evoked during oxidative stress conditions [45].…”
Section: Er Stress and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Nrf1 and Nrf3 proteins of this family have been reported to be associated with the ER membrane and nuclear envelope which suggest their involvement in ER-related functions [43,44]. A study in Caenorhabditis elegans [45] revealed that SKN-1, the Nrf ortholog, plays a critical role in resistance to oxidative and ER stress. Moreover, it has been reported that the response mobilized by SKN-1/Nrf under UPR is observed to be overlapping but still distinct from that evoked during oxidative stress conditions [45].…”
Section: Er Stress and Oxidative Stressmentioning
confidence: 99%
“…A study in Caenorhabditis elegans [45] revealed that SKN-1, the Nrf ortholog, plays a critical role in resistance to oxidative and ER stress. Moreover, it has been reported that the response mobilized by SKN-1/Nrf under UPR is observed to be overlapping but still distinct from that evoked during oxidative stress conditions [45]. SKN-1/ Nrf is reported to be activated by ER stress, independent of ROS signaling, and it provides resistance against reductive stress as well [45].…”
Section: Er Stress and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing hsp-4 mRNA levels and using an hsp-4::gfp reporter it was confirmed that knockdown of ero-1 leads to UPR ER activation. 54,56,57 These findings indicate that the oxidases and PDIs play a central role in maintaining proteostasis of the ER.…”
Section: The Crucial Role Of Pdi's and Ero-1 To Maintain Er Homeostasmentioning
confidence: 92%
“…In plants, exploration of specific basic leucine zipper (bZIP) oxidative stress transcription factors has mostly focused on the TGA bZIP family, which bears some resemblance to the yeast (Saccharomyces cerevisiae) phase II detoxification factor YEAST AP-1-LIKE (Johnson et al, 2001;Després et al, 2003). In the animal kingdom, many stress transcription factors are utilized during oxidative stress to activate protective responses (bZIP transcription factors X-BOX BINDING PROTEIN1, ACTIVATING TRANSCRIPTION FACTOR4 [ATF4], NF-E2-RELATED FACTOR1-3, and ATF6; An and Blackwell, 2003;Harding et al, 2003;Glover-Cutter et al, 2013), with many of these factors playing intersecting roles in related cellular stresses, including protein homeostasis and aging (Henis-Korenblit et al, 2010;Kenyon, 2010;Hetz, 2012).…”
mentioning
confidence: 99%